Word order of some English and Waray clauses a descriptive contrastive analysis - Araullo, Adelaida Arena 1925- (1969)
In this study, the researcher attempted to present and describe the word order of some English clauses, to present and describe the word order of some Waray clauses, and to make a contrastive analysis of the word order of English and Waray clauses. Through the contrastive analysis, it was revealed that English and Waray clauses differ in form but not in meaning and distribution. Waray clauses are more flexible with regard to the position of some of its parts. A Waray learner of English who has not fully learned the language will tend to apply the word order of Waray clauses in English clauses.